2018
DOI: 10.1111/ajt.14632
|View full text |Cite
|
Sign up to set email alerts
|

The TWEAK/Fn14 pathway is required for calcineurin inhibitor toxicity of the kidneys

Abstract: Calcineurin inhibitor toxicity (CNT) is a frequent occurrence in transplanted renal grafts and autochthone kidneys from patients undergoing long-term treatment with calcineurin inhibitors, notably cyclosporin A (CsA) and tacrolimus. Here, we show an indispensable role of the tumor necrosis factor superfamily (TNFS) molecule TNF-related weak inducer of apoptosis (TWEAK) (TNFSF12) in the pathogenesis of acute CNT lesions in mice. A deficiency in TWEAK resulted in limited tubulotoxicity after CsA exposure, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…In our cell culture model, the viability of NRK tubular epithelial cells significantly decreased when cells were incubated with Tac according to the PK profiles of fast metabolizers (Figure 6). These most affected cells notably expressed the highest amount of Fn14, a receptor protein known to be involved in the pathogenesis of CNIT [3]. It has to be considered that due to the robustness of NRK cells we applied Tac concentrations that are supra-therapeutic compared to Tac blood concentrations that are observed in patients and a direct translation into clinical practice and exact modelling of patients’ Tac exposure, which is much more complex and influenced by many factors in vivo, is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our cell culture model, the viability of NRK tubular epithelial cells significantly decreased when cells were incubated with Tac according to the PK profiles of fast metabolizers (Figure 6). These most affected cells notably expressed the highest amount of Fn14, a receptor protein known to be involved in the pathogenesis of CNIT [3]. It has to be considered that due to the robustness of NRK cells we applied Tac concentrations that are supra-therapeutic compared to Tac blood concentrations that are observed in patients and a direct translation into clinical practice and exact modelling of patients’ Tac exposure, which is much more complex and influenced by many factors in vivo, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…As fibroblast growth factor-inducible 14 (Fn14) is involved in the pathogenesis of CNIT we analyzed its expression in Tac-treated NRK cells using primary antibodies against α-actinin 4 and Fn14, respectively [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fn14 expression is relatively low in normal healthy tissues, while it could be rapidly activated in response to stress stimuli, which represents one of the main regulatory mechanisms for evoking inflammation or apoptosis. Activation of Fn14 by recombinant TWEAK (rTWEAK) mediates tubular damage and nephrotoxicity upon cyclosporin A (CsA) exposure [5]. Fn14 deficiency attenuates kidney IgG deposition, decreases inflammatory cell infiltration, and protects mice from developing lupus nephritis [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Calcineurin inhibitor (CNI)-related nephrotoxicity occurs in up to 35% of recipients and it has been proposed that all recipients using CNIs eventually develop histological lesions consistent with toxicity in their allografts. 6 A review of 12 studies showed that the risk of CNI-related new onset diabetes after transplantation (NODAT) ranges from 2 to 50%. 7 Though there are several associated risk factors for NODAT, the biological basis is currently unknown.…”
Section: Introductionmentioning
confidence: 99%